Designing Oil and Gas Exploration Strategy For The Future National Energy Sustainability Based on Statistical Analysis of Commercial Reserves and Production Cost in Indonesia - Ahmad Abdul Azizurrofi; Dian Permatasari Mashari (Indonesian Journal of Energy, 2018)
Indonesia's declining oil production and rising domestic oil consumption have been a big issue for the last few decades which has turned Indonesia into a net oil importer from 2004 onward. The lack of exploration activities and other investments in oil and gas sector have resulted in the decline of Indonesia's oil production. This condition is a result of the plunge of global oil price which has fallen to its lowest level, i.e., US$43.14/Bbl (average oil price in 2016) over the last 12 years. The purpose of this paper is to analyze the distribution of oil and gas production in Indonesia along with the production cost. This analysis will allow investors to find and map working areas in Indonesia with potential commercial reserves while maintaining the lowest possible production costs. The approach of this empirical study is to divide Indonesia into 6 (six) geographical areas, namely Sumatera, Natuna Sea, Java, Kalimantan, Sulawesi and Papua. We have collected relevant data about commercial reserves and production cost from existing working areas. Our preliminary results depict that Kalimantan has the highest commercial reserves (i.e., 18.60 MMBOE per contract area) and Papua has the lowest production cost (i.e., US$3.24/BOE). Sulawesi, meanwhile, has the lowest commercial reserves (i.e., 5.39 MMBOE/Contract Area) and Natuna has the highest production cost (i.e., US$16.46/BOE). In summary, this study has shown that Eastern area of Indonesia might hold more oil and gas reserves which can be further managed by Contractor for the benefit of the Country. This study also recommends the Government of Indonesia to be aware of the condition of each working areas to maintain a sustainable oil and gas production on a National level and create attractiveness for investors in the future.